The Development Of Indonesian Islamic Civilization During The Dutch Occupation - Aisya Hanum; Muhammad Ihsan; Nasikhin; Fihris (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This study aims to analyze the development of Indonesian Islamic civilization during the Dutch colonial period. To achieve this goal, the authors use the literary method with a qualitative approach, namely by collecting data and information by examining various sources in the form of books or scientific papers that are relevant to the object of research. With this research shows that 1). The socio-cultural conditions during the Dutch period underwent changes which can be seen by the existence of social discrimination and the presence of Dutch culture that entered Indonesia. 2). The system of government that prevailed in Indonesia during the Dutch colonial period. 3). Da'wah strategy carried out by the scholars during the Dutch colonial period. 4). Challenges faced by Indonesia during the Dutch colonial period. 5). An influential figure during the Dutch colonial period. This study is important to do in order to add to the study of the history of Islamic civilization in Indonesia, especially the scarcity of themes that discuss Islamic civilization during the Dutch colonial period.